2022
DOI: 10.3390/educsci12070464
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Key Digital Transformation Lessons for Higher Education Institutions in South Africa

Abstract: COVID-19 has left an unmistakable impression on the world stage. It has altered the global socio-economic landscape, forcing individuals to adapt and embrace new ways of doing business, as well as new ways of life. One of the most significant effects of the pandemic was to hasten the adoption of digital technologies by many areas of the global economy. Campus closures were observed in the higher education sector, putting an end to long-standing face-to-face teaching and learning. This necessitated the most rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 39 publications
(78 reference statements)
0
11
1
Order By: Relevance
“…Many innovations were implemented including use of social media, Televisions, zoom., Microsoft teams, google teams to disseminate information that could of more importance to knowledge sharing between the instructor and student. However, the cost of internet, internet devices and the ability to use this technology were major obstacles to use e-learning for universities [4,5,7]. Given such interesting insights, the current study seeks to investigate the technological innovations that universities implemented during the Corona virus pandemic period.…”
Section: Problem Statementmentioning
confidence: 99%
“…Many innovations were implemented including use of social media, Televisions, zoom., Microsoft teams, google teams to disseminate information that could of more importance to knowledge sharing between the instructor and student. However, the cost of internet, internet devices and the ability to use this technology were major obstacles to use e-learning for universities [4,5,7]. Given such interesting insights, the current study seeks to investigate the technological innovations that universities implemented during the Corona virus pandemic period.…”
Section: Problem Statementmentioning
confidence: 99%
“…There are some prior studies have explored issues about digital transformation resulting from the COVID-19 pandemic: Abdulrahim and Mabrouk (2020), Bhagat and Kim (2020), Marks et al (2020), García-Morales et al (2021, Hai et al (2021), Kutnjak (2021), Mahmud et al (2022), andNurhas et al (2021) have highlighted the challenges of rapid digital transformation in higher education institutions during the global pandemic. Mahmud et al (2021) and Mhlanga et al (2022) have concluded key digital transformation lessons learned during the pandemic. However, the diffusion of digitalization that happened during the COVID-19 outbreak has also brought new opportunities to higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, understanding the ethical and methodological issues of digital storytelling among the study population of first-year university students can inform the design of public health studies using the digital storytelling method. Such research can inform how more diverse university students can be engaged in digital storytelling, given that youths have been found to be active users of online platforms [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%